2020
DOI: 10.1111/epi.16595
|View full text |Cite
|
Sign up to set email alerts
|

Drebrin expression patterns in patients with refractory temporal lobe epilepsy and hippocampal sclerosis

Abstract: Objective: Drebrins are crucial for synaptic function and dendritic spine development, remodeling, and maintenance. In temporal lobe epilepsy (TLE) patients, a significant hippocampal synaptic reorganization occurs, and synaptic reorganization has been associated with hippocampal hyperexcitability. This study aimed to evaluate, in TLE patients, the hippocampal expression of drebrin using immunohistochemistry with DAS2 or M2F6 antibodies that recognize adult (drebrin A) or adult and embryonic (pan-drebrin) isof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
(67 reference statements)
1
5
0
Order By: Relevance
“…These findings suggest that epilepsy patients have less stable actin filaments within their spines. In line with this, a recent study found that lower drebrin levels in the hippocampi of temporal lobe epilepsy patients were associated with higher seizure frequency and less neuron survival 17 . These dendritic changes may represent a trait in the pathophysiology of seizure development or a consequence of them or even a compensatory response as a form of homeostatic plasticity to dampen excessive neuronal excitability 14 .…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…These findings suggest that epilepsy patients have less stable actin filaments within their spines. In line with this, a recent study found that lower drebrin levels in the hippocampi of temporal lobe epilepsy patients were associated with higher seizure frequency and less neuron survival 17 . These dendritic changes may represent a trait in the pathophysiology of seizure development or a consequence of them or even a compensatory response as a form of homeostatic plasticity to dampen excessive neuronal excitability 14 .…”
Section: Discussionsupporting
confidence: 55%
“…The initial reduction was followed by the recovery of drebrin levels in the chronic phase of pilocarpine-induced seizures suggesting the crucial role of drebrin in reactive synaptic plasticity 18 , 19 . Another recent study, showed a negative correlation between drebrin expression and seizure frequency in particular in the dentate gyrus 17 . Taken together it is difficult to conclude on a linear correlation between drebrin expression and seizure susceptibility.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…They also studied whether neuron density differs between TLE patients with and without depression. Their study follows up on previous reports on histopathological differences between patients with and without psychiatric comorbidities in general (Kandratavicius et al, 2012a(Kandratavicius et al, , 2014(Kandratavicius et al, , 2015 and between types of hippocampal sclerosis and epilepsy-related factors (Coras et al, 2014;Thom, 2014;Rodrigues et al, 2015;Dombroski et al, 2020).…”
mentioning
confidence: 76%
“…Even if more HS type 1 cases where added, we believe stronger associations would emerge. Apart from HS types, we know that even the same HS type can had differential synaptic reorganization in several regions ( Dombroski et al, 2020 ). It would be interesting to see if these, changes could impact MTR in higher field MRI, with smaller voxel sizes and subfield MTR assessment.…”
Section: Discussionmentioning
confidence: 99%